Macronutrient Digestibilities and Enzyme Activities in Rumen Fluid Supplemented by Protein-Energy Synchronized Index-Based Rations - Afduha Nurus Syamsi; Harwanto Harwanto; Hermawan Setyo Widodo; Yusuf Subagyo (Buletin Peternakan, 2022)
The protein-energy  synchronized  (PES)  index-based  rations  can  optimize microbial  protein  synthesis  (MPS)   and   affect   enzyme   activity   and  macronutrient digestibility of ration in rumen fluid. This study aimed to examine the in vitro effect of a ration based on PES index on macronutrient digestibility and enzyme activity in rumen fluid. The research was conducted experimentally, consisting of 4 treatment rations with different  PES  indexes  (R1:  0.55;  R2:  0.6;  R3:  0.65;  R4:  0.7).  Each  treatment  was repeated 5 times, so there were 24 experimental units. The material used was the rumen fluid of the Jawa Randu Goat, which was taken at the Sokaraja Slaughterhouse shortly after  the  goat  was  slaughtered.  Each  ration consisted  of  napier  grass,  river  tamarind, coconut  meal, soybean  dregs,  rice  bran,  cassava  waste,  and  mineral  mix.  The  results showed  that  the  PES  index  significantly  affected  (P<0,01)  the  digestibility  of  protein (A),  fiber  (B),  and  fat  (C),  as  well  as  the  activity  of  protease  (D)  and  cellulase  (E) enzymes.  Theorthogonal  polynomial  test  showed  that  the  PES  index  has  a  quadratic effect on all test parameters with the following equation: A (Y= -1229.5X2 + 1540.6X -457.57; R2= 0.75), B (Y = -800.95X2+ 955.86X -264.51; R² = 0.75), C (Y = 868.92X2-1038.2X + 325.1; R2= 0.81), D (Y = -41.4X2+ 51.697X -14.982; R² = 0.77), and E (Y = -4.8538X2+  5.927X -1.6241;  R²  =  0.84).  The  protein-energy  synchronized  index-based rations increased the in vitro of macronutrient digestibility (protein, fiber, and fat) and enzyme activity on rumen fluid at a medium index level (0.6-0.63).